Athletes Welfare and Reward System in Indonesia: The 30th SEA Games 2019 Athletes and Coaches Perspective - Novan, Novrizal Achmad; Nuryadi, N; Komarudin, K (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
Sports heroes are considered worthy of appreciation, especially for those who contribute to providing achievements for the nation at regional and international levels. The reward is given to athletes and coaches during their productive lives in the present until their retirement period. However, the rewards received by athletes and coaches tend not to be able to fulfill their welfare as a guarantee of life in the future. Therefore, this study was aimed at determining the relationship between rewards and the level of welfare given by the government and sports committees in Indonesia to athletes and coaches. This research was an ex-post-facto study using a self-administered closed-questionnaire conducted on athletes and national coaches on the 30th SEA Games team in Philippines in 2019. The number of samples was determined by using Slovin formula at 5% error rate and carried out on 46 athletes and nine coaches under the authority of the Indonesian National Sports Committee in Bandung. Data analysis was performed by using SPSS. From the results obtained, these rewards also had a direct correlation with the level of welfare of athletes and coaches. Considering that, if a maximum reward is given, the level of welfare will also be increased. The results indicates that there is a robust and significant positive relationship between rewards and welfare. Athletes and coaches expected the government and sports committee in Indonesia to give rewards that are not only limited to bonuses in terms of financial. Other aspects also need a concern when the athletes and coaches are no longer productive in contributing to the national sports achievements.